Speed is nothing... without control, about fitness as well! - Sartori, S.; Ardigo, L. P.; Motta, S.; Padulo, J. (V International Congress "Ligaments and Tendons - Research and Clinical practice" - Salerno (Italy) December 4/5 2015, 2015)
In the last decade the focus on movement speed control has deserved increasing interest in the literature (1). Movement speed control has showed to mirror technical skill and fitness level in exercises/activities requiring particular technical skills. Furthermore, such assessment avoids administering potential dangerous maximum effort protocols to non-athletes. Therefore the aim of this study was to assess movement speed control at a common isotonic machine and with two sub-maximal loads.. Available from: https://www.researchgate.net/publication/287162300_Speed_is_nothing_without_control_about_fitness_as_well [accessed Dec 18, 2015].